Low cost-hydroponics systems for urban and peri-urban farming - Singh, S R; Kumar, Dinesh; Babu, Naresh; Soni, Vijai (Indian Horticulture, 2026)
Urbanization and rapid industrialization are shrinking natural resources, while the ever-growing population suffers from malnutrition instead of enjoying guaranteed food security for every citizen of India. This situation necessitates adopting innovative approaches to ensure food and nutritional security. Hydroponics, a soilless farming technology, offers significant advantages, such as higher water use efficiency, pesticide-free production, and suitability for limited spaces. While high-tech hydroponics systems are often capital-intensive, low-cost hydroponic models using locally available materials—such as plastic bags, scrap containers, PVC pipes, polythene tubes, and coconut coir—can be effectively adopted for urban horticulture. ICAR-CISH Lucknow has developed low-cost designs using inexpensive materials in liquid and aggregate hydroponics, enabling year-round production of vegetables, herbs, and small fruits on rooftops and balconies. Promoting low-cost hydroponics can transform urban horticulture, enhance livelihoods, and contribute to a sustainable urban food system.